Activity, Profitability Indictors Analysis: A Comparsion Study among Nationality and Iraqi Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Reseach target the most important topic, is Activity and ProfitabilityIndictors Analysis forNationality and Iraqi Insurance Company, In order to stand on them ability to cover its risksand explore the efficiency asset and its avialible resources using to determine them abilities toprofit generation from its insurance activity. The analysis was focus to examine their profitand activity power, and test the significant differences aming them performance. Test 2hypothese that is related and result it sign that the 2 company no has significant differences atprofitability and activity level. The research depend on coneclusion, recommended twocompany to work at efficiency with cost element of insurance activity in order to maximizethe insurance surpluse average, by using the successful viechals to insurance servicesmarketing to large number of insurance applicatoers according to apply the electronicmanagement requirement